Window shopping model to develop student's religious moderation literacy - Slam, Zaenul; Rozak, Abd (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Religious diversity is a significant aspect of contemporary society, with individuals adhering to various faiths and belief systems. Promoting religious moderation among students in educational settings is crucial to fostering an inclusive and harmonious environment that respects diverse religious perspectives. Student's religious moderation literacy is inseparable from various factors. This study aimed to determine how the window-shopping model developed students' religious moderation literacy. This study was motivated by diminishing religious moderation literacy among students. This study was conducted qualitatively by using a case study. The results showed that through the window-shopping model, student's religious moderation literacy could be developed. In addition, the window-shopping model could teach students to be independent, collaborative, critical, and creative. This study is recommended to optimize the window-shopping model as a learning model that can develop various student potencies.